2017
DOI: 10.1093/brain/awx316
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity of right frontal hyperactive areas scales with stuttering severity

Abstract: Persistent stuttering reflects atypical brain activity and connectivity, most notably within the left hemisphere speech production networks. Neef et al. link right frontal overactivations common to stuttering to structural networks that support right hemisphere specialisations. In particular, severe stuttering reflects increased activity in a global motor response inhibition network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
110
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 111 publications
20
110
2
1
Order By: Relevance
“…Further studies reported that the disorganisation extended into ventral premotor cortex, bilaterally, and corresponded to abnormalities in functional activation of nearby grey matter in adolescents and young adults who stutter (Watkins, Smith, Davis, & Howell, ). In adults who stutter, the right hemisphere disruptions underlying ventral premotor tracts correspond to hyperactivity during imagined speech tasks in fMRI and correlate with stuttering severity (Neef et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies reported that the disorganisation extended into ventral premotor cortex, bilaterally, and corresponded to abnormalities in functional activation of nearby grey matter in adolescents and young adults who stutter (Watkins, Smith, Davis, & Howell, ). In adults who stutter, the right hemisphere disruptions underlying ventral premotor tracts correspond to hyperactivity during imagined speech tasks in fMRI and correlate with stuttering severity (Neef et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, overactivation of this pathway results in increased global inhibition of motor systems, which in turn disrupts control of ongoing and succeeding motor programs for fluent speech . It must also be noted that a recent study revealed altered structural abnormalities in the white matter pathway connecting the right frontal regions with the pre‐SMA, as well as with subcortical structures . Therefore, it is possible that reduced stuttering by tDCS involving a cathode over RB in our study might be a consequence of indirect modulation of dysfunctional activity in the basal ganglia and/or right SMA, which are connected to the RB.…”
Section: Discussionmentioning
confidence: 75%
“…Some evidence indicates this is the case for the FAT's involvement in stuttering. Thus, a recent study by Neef and colleagues (Neef et al., ) showed that stronger structural connectivity of the right, but not left, FAT is associated with worse stuttering. They interpreted this as indication of hyperactivity of the network involved in global response suppression, which disrupts fluent speech that typically relies strongly on left perisylvian networks, supported by the left FAT and associated perisylvian pathways.…”
Section: Discussionmentioning
confidence: 95%
“…It has also been proposed that a primary deficit in ADHD is in fact one of inhibitory control (Barkley, 1997;Neely et al, 2017;Schachar, Mota, Logan, Tannock, & Klim, 2000). However, inhibitory control and more broadly defined executive function deficits are not a universal feature of ADHD (Nigg, Willcutt, Doyle, & Sonuga-Barke, 2005), and in fact there may be executive function subtypes of ADHD, with an inhibitory control dysfunction profile describing only one of the subtypes (Roberts, Martel, & Nigg, 2017 (Neef et al, 2018) showed that stronger structural connectivity of the right, but not left, FAT is associated with worse stuttering.…”
Section: The Role Of the Frontal Aslant Tract In Externalizing Behamentioning
confidence: 99%